The Implementation of Warehouse Management System (WMS) at CV. Everfresh Kediri - Rachmawati, Putri Indah; Handayani, Wiwik (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Warehouse Management System (WMS) as software to improve the efficiency of warehouse management. Warehouse management systems require solutions to optimise the management of accurate inventory data to record every transaction in the warehouse, manage the way goods are stored, and integrate between warehouses. CV. Everfresh Kediri is a manufacturing company engaged in seed production. The problems identified in warehouse operations mostly come from human error. This research was conducted to improve warehouse operational management by developing a Warehouse Management System (WMS) using the myWMS application as the right solution to reduce human error by implementing various management processes, including inbound and outbound management and tracking, as well as visualizing the time of each process that occurs from goods entering to exiting the warehouse. Testing using the FIFO LIFO method with myWMS software shows that the FIFO method is the best choice for the company because it can streamline the operational process up to 10 Minutes 18 Seconds or 20.04% from the old manual process.